Development of bright and dark pulsed fiber laser based on nonlinear polarization rotation / Tiu Zian Cheak - Tiu, Zian Cheak (2015)
Pulsed lasers have many practical applications in both communication and sensing. This thesis describes in detail the generation of bright pulses and dark pulses lasers based on nonlinear polarization rotation (NPR). The passive techniques are explored for pulse generation as they are reliable, compact, producing high beam quality and do not require an external modulator. Various techniques such as film saturable absorber (SAs), fiber SA and NPR techniques are studied to generate pulse. Performance of graphene SA in Erbium-doped fiber laser (EDFL) with three different gain mediums is successfully demonstrated. Q-switched EDFL are also demonstrated using thulium-doped fiber as a SA. NPR technique is adopted in a ring EDFL to generate Q-switched with low pump power. Besides the Q-switching operation, NPR technique is also explored to generate mode-locked, harmonic mode-locked, and multi-wavelength mode-locked. On the other hand, nonlinear Schrödinger equation (NLSE) dark pulse, cubic-quintic nonlinear Schrödinger equation (CQNLSE) dark pulse and domain wall (DW) dark pulse are demonstrated under different EDFL cavities based on NPR technique. Furthermore, multi-wavelength dark pulse is achieved using PCF in figure-of-eight cavity to slice the dark pulse spectrum. Besides, Q-switched dark pulse is achieved in an unstable mode-locking operation, in which the Q-switching operation modulated the dark pulses.